Hubungan Body Image dengan Kecemasan Sosial Pada Dewasa Awal - Rima Muharram; Cut Ita Zahara; Ika Amalia (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2020)
The aims of this study was to determine the relationship between body image and social anxiety in early adulthood. Social anxiety is described as an individual's fear of performance and socially related physical situations that make individuals more careful about the people around them. The study sample used 100 early adult respondents aged 18-25 years, selected through cluster sampling. Data collection is done by body image scale and social anxiety. Data analysis using the product moment technique from Pearson. The results showed a positive relationship between body image and social anxiety in early adulthood, with a correlation coefficient of 0.699 (p = 0.000 <0.05).